Preparing Nanosilica Particles from Rice Husk Using Precipitation Method - Rusel Zahraw Farhan; Shahlaa Esmail Ebrahim (مجلة بغداد للعلوم, 2021)
Nanosilica was extracted from rice husk, which was locally collected from the Iraqi mill at Al-Mishikhab district in Najaf Governorate, Iraq. The precipitation method was used to prepared Nanosilica powder from rice husk ash, after treating it thermally at 700°C, followed by dissolving the silica in the alkaline solution and getting a sodium silicate solution. Two samples of the final solution were collected to study the effect of filtration on the purity of the sample by X-ray fluorescence spectrometry (XRF). The result shows that the filtered samples have purity above  while the non-filtered sample purity was around  The structure analysis investigated by the X-ray diffraction (XRD), found that the Nanosilica powder has an amorphous structure in nature. Also, it shows a broad peak at (    The particle size distribution was determined by Atomic force microscope (AFM), the results gave that the average diameter equals  and dimension range in , while B.E.T. analysis confirms a high surface area around 618 . FT-IR Spectra experimental data showed the presence of hydrogen-bonded silanol group (Si–O–H) and siloxane group (Si–O–Si) which proved the high purity of Nanosilica particles.